Cardiac magnetic resonance imaging unmasks presumed embolic myocardial infarction due to patent foramen ovale case report. Issue 2 (1st February 2022) - Liang, Kate; Williams, Matthew; Bucciarelli-Ducci, Chiara
Abstract: Background: Occurrence of paradoxical coronary embolism is reported in up to 10–15% of all myocardial infarctions but embolic infarctions presumed to be as a result of a patent foramen ovale (PFO) are rare. Although rare, it is important to identify these patients as they need appropriate investigations to confirm their diagnosis and guide further treatment. Case summary: We present the case of a gentleman with troponin positive chest pain with non-obstructed coronaries on invasive coronary angiogram. Subsequent cardiac magnetic resonance imaging (MRI) demonstrated multi-focal myocardial infarctions in several coronary artery territories. Further investigations including echocardiogram were performed in order to identify a cause and source of the embolic infarctions and led to the diagnosis of patent foramen ovale. The patient was treated as myocardial infarction with non-obstructed coronary arteries most likely due to embolic phenomena in the presence of a PFO. Conclusion: Multiple focal infarctions in multiple coronary artery territories should raise the suspicion of an intra-cardiac shunt. Multi-modality imaging with cardiac MRI and echocardiogram is important in correctly identifying any source of emboli and the diagnosis of any intra-cardiac shunt. Whilst PFO closure is a possible treatment for patients, considerations regarding risk stratification and local provisions needs to be taken into account. Patients should be referred to the appropriate subspecialist to ensure suitable long-term follow-up.